2013
DOI: 10.4049/jimmunol.1301490
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reactive Oxygen Species Induces NLRP3-Dependent Lysosomal Damage and Inflammasome Activation

Abstract: The NLRP3 inflammasome drives many inflammatory processes and mediates IL-1 family cytokine release. Inflammasome activators typically damage cells, and may release lysosomal and mitochondrial products into the cytosol. Macrophages triggered by the NLRP3 inflammasome activator nigericin show reduced mitochondrial function and decreased cellular ATP. Release of mitochondrial ROS leads to subsequent lysosomal membrane permeabilization (LMP). NLRP3-deficient macrophages show comparable reduced mitochondrial funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
337
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(350 citation statements)
references
References 37 publications
9
337
0
4
Order By: Relevance
“…S100A8/S100A9 heterodimers activate both NF-kB and NLRP3 inflammasome assembly via a NOX/ROS-dependent mechanism. 23,[44][45][46] Intracellularly, S100A8/9 heterodimers serve as a scaffold for the membrane assembly and activation of the NOX complex, 47,48 which generates ROS via transfer of electrons across membranes to generate superoxide. 49 As also shown here, NOX regulates both priming and activation of NLRP3 inflammasomes, including the activation of caspase-1 and IL-1b secretion.…”
Section: Discussionmentioning
confidence: 99%
“…S100A8/S100A9 heterodimers activate both NF-kB and NLRP3 inflammasome assembly via a NOX/ROS-dependent mechanism. 23,[44][45][46] Intracellularly, S100A8/9 heterodimers serve as a scaffold for the membrane assembly and activation of the NOX complex, 47,48 which generates ROS via transfer of electrons across membranes to generate superoxide. 49 As also shown here, NOX regulates both priming and activation of NLRP3 inflammasomes, including the activation of caspase-1 and IL-1b secretion.…”
Section: Discussionmentioning
confidence: 99%
“…67 Previous studies showed that ROS, especially those from mitochondria, contributed to activation of the NLRP3 inflammasome. 10,12,[68][69][70] Indeed, numerous NLRP3 inflammasome activators are known to trigger mitochondrial ROS production in a variety of cells. For example, the saturated fatty acid palmitate leads to the activation of the NLRP3 inflammasome and release of active IL-1b in a mitochondrial ROS-dependent manner.…”
Section: Molecular Mechanisms Of the Canonical Activation Of The Nlrpmentioning
confidence: 99%
“…Several molecular mechanisms have been suggested for NLRP3 activation to induce caspase-1 activation and IL-1b maturation. These include pore formation and potassium (K 1 ) efflux, 7,8 lysosomal destabilization and rupture, 9,10 and mitochondrial reactive oxygen species (ROS) generation. [10][11][12] Evidence supports that the aberrant activation of the NLRP3 inflammasome is associated with the pathogenesis of various autoinflammatory, autoimmune, and chronic inflammatory and metabolic diseases, including gout, atherosclerosis, and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also increasing evidence that inflammasome activation triggered by different stimuli, including bacterial toxins, silica crystals, aluminum salts, lipofuscin and lysosomotropic detergent LeuLeuOMe (Hornung et al, 2008;Duewell et al, 2010;Tseng et al, 2013), cholesterol crystals (Duewell et al, 2010), and mitochondrial ROS (Heid et al, 2013) is accompanied by LMP. For example, Bacillus anthracis lethal toxin (LT) triggers NLRs and also induces LMP in macrophages, which results in pyroptotic cell death.…”
Section: Pyroptosismentioning
confidence: 99%